MATHEMATICAL MODELING OF DYNAMICS OF CURVED PIPES CONVEYING INTERNAL MASSES OF NONHOMOGENEOUS LIQUID - Tolbatov, Yevgeniy (Proceedings of National Aviation University (archive), 2015)
The article considers computer simulation of dynamics of elastic tube serpentines with internal flows of boiling liquids. We propose the motion model of non-homogeneous boiling liquid clots. The technique of numerical solution of the constructed equations is based on the transfer matrix method.